Effect of nozzle turbulent intensity in multiple round jets using openFOAM®. Issue 2 (August 2020) - Kannan, B T; Gaur, Nikhil; Balakrishnan, P
Abstract: The present work is about the effects of turbulent intensity on the flow field of turbulent multiple jets. The simulations are carried out by using an open-source Computational Fluid Dynamics C++ code OpenFOAM®. The governing equations invoked are Reynolds Averaged Navier Stokes equations by using simpleFoam solver. The standard two-equation turbulence model is used along with the mean flow equations to account for turbulence effects. The solved flow field shows a significant effect of turbulent intensity on the potential core of both single and multiple jets which is supported by reference literature. Downstream the potential core, the turbulence intensity does not affect the decay rate of turbulent jets considered in the study. The performance parameters show that the higher initial values of turbulent intensity is favorable only for the single jet simulations. In contrast, the lower initial values of turbulent intensity is favorable for multiple jet simulations.